Upaya Pemahaman Konsep Keragaman Budaya di Indonesia dengan Model Pembelajaran Berbasis Budaya Lokal di Kelas IV SDN Bendogerit 2 Kota Blitar - Rini Setyowati (IJoIS: Indonesian Journal of Islamic Studies, 2021)
Abstract. Indonesia has many cultures, traditions, and customs that are not widely known by the younger generation. Cultures and traditions that are believed to be passed down from generation to generation and are the nation's identity must be maintained and preserved by the nation's successors. The teacher is a means for students to introduce regional cultures in Indonesia, because in this day and age many foreign cultures have been recognized by students, so students forget the local culture in the student area. In Thematic learning in Grade IV Elementary School, the Social Sciences (IPS) subject is taught about cultural diversity in Indonesia, for this reason, qualitative research is needed on students in learning Cultural Diversity in Indonesia. The type of research used is Classroom Action Research (CAR). Data analysis techniques used are data reduction, data presentation, and drawing conclusions.